Antioxidant Potential Profile of Extracts from Different Parts of Black Mulberry - IQBAL, SADAF; NADEEM ASGHAR*†, MUHAMMAD; ULLAH KHAN, ISLAM; ZIA, IRAM (Asian Journal of Chemistry, 2009)
Present study is aimed to exploit a potent and cheaper natural sources ofantioxidants. Morus nigra L. is considered to be an antidiabetic and diureticagent in the folk medicinal system of Indo-Pak subcontinent. Antioxidantpotential and radical scavenging activity of the various organic and aqueousextracts of leaves, stem and fruit of M. nigra were investigated using 2,2'-azinobis(3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) decolourizationassay, ferric reducing antioxidant power (FRAP) assay, 2.2'-diphenyl-1-picrylhydrazyl(DPPH) assay, total phenolic content (TPC) assay and total antioxidantactivity assay. Using ABTS•+ decolourization assay and FRAP assay, M.nigra extracts showed a wide range of antioxidant activity. Using TPC assaythe amount of total phenolics ranged from 1.3048 to 5.8287, 0.413 to 2.9394and 0.5346 to 6.2266 mg/L for different fractions of leaves, stem and fruit ofM. nigra, respectively. Good co-relation was found between TPCs and TEACvalues determined by ABTS•+ decolourization assay (r2 = 0.977, 0.943 and0.823 for leaves, stem and the fruit of stem and FRAP assay (r2 = 0.887,0.842 and 0.773 for leaves, stem and the fruit) of M. nigra. Employing totalantioxidant assay using linoleic acid emulsion system, methanol, 1-butanol,aqueous and ethyl acetate fractions of all the parts of M. nigra showed strongperoxyl radicals scavenging activity. The data obtained by employing antioxidantand radical scavenging assays demonstrated the effectiveness of allthe parts of M. nigra as antioxidative and radical scavenging which may alsobe correlated with its anti-disease activity in in vivo.